Jose Rizal - Claudio, Lisandro E. author. aut Link
XVII, 89 p.
Keywords: The global history of liberalism has paid too much attention to the West, neglecting the contributions of liberals from colonial nations. This book mines the thought of Filipino propagandist and novelist, Jose Rizal, to present a vision of liberalism for the colonized. It is both an introduction to Rizal and a treatise on rights, freedom, and tyranny in colonial contexts. Though a work on history, it responds to the illiberal present of rising authoritarianism and populism. Lisandro E. Claudio is Associate Professor at De La Salle University Manila’s College of Liberal Arts, Philippines, and teaches courses in History and Literature. He is the author of Liberalism and the Postcolony: Thinking the State in 20th-Century Philippines. .